Kebiasaan Mencicipi Pestisida, Pemakaian APD dan Kadar Kholinesterase pada Petani di Desa Gajah Pokki Kecamatan Purba Kabupaten Simalungun - Marlinang Isabella Silalahi; Eva Ellya Sibagariang; Annete M. Tambunan; Habsah Ritonga; Nisa K. Pasaribu (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
The use of pesticides is still very important in agriculture and plantations, because the control of pests that can damage agricultural products is very effective with pesticides. However, in applying it, it is often not in accordance with procedures, thus putting farmers at risk of being exposed to pesticides and being exposed in the long term. The habit of farmers in Gajah Pokki Village in tasting pesticides before they are applied is also worrying because pesticides enter the body directly orally. This study aims to determine the habit of tasting pesticides, wearing PPE and cholinesterase levels in farmers in Gajah Pokki Village, Purba District, Simalungun Regency. Pesticide subject is a farmer group of 20 people. The results showed that there were as many as 17 people (85%) of farmers who tasted pesticides, then 18 people who used gloves (90%), 17 people with masks (85%) and 18 people with eye protection (90%) . However, 19 people (95%) wore head protection and work clothes and 18 people (90%). Meanwhile, on blood examination to see cholinesterase levels, 7 people (35%) had abnormal cholinesterase levels.